1995
DOI: 10.3109/00365519509075372
|View full text |Cite
|
Sign up to set email alerts
|

Random capillary whole blood glucose test as a screening test for diabetes mellitus in a middleaged population

Abstract: This study was aimed at assessing the adequacy of a random capillary whole blood glucose (RCBG) test as a screening test for diabetes mellitus in a middle-aged (55-year-old) Finnish population. Both the screening test (RCBG) and a standard 2-h oral glucose tolerance test (OGTT) were performed on all the participants according to the WHO criteria. The prevalence based on the 2-h OGTTs was 8.5% (11.7% for men and 6.0% for women). The sensitivity, specificity and predictive values of the screening test for diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The optimal cut‐off ranged from 4.4 to 6.7 mmol/l (80–120 mg/dl), but still the sensitivity ranged from 67% to 83% and specificity from 65% to 80%. Similar results have been reported from other groups [17]. Due to these problems with standardization and the relatively low sensitivity and specificity, random blood glucose alone is of limited value as a screening test for diabetes.…”
Section: Is There An Accepted Screening Test and Diagnostic Test For mentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal cut‐off ranged from 4.4 to 6.7 mmol/l (80–120 mg/dl), but still the sensitivity ranged from 67% to 83% and specificity from 65% to 80%. Similar results have been reported from other groups [17]. Due to these problems with standardization and the relatively low sensitivity and specificity, random blood glucose alone is of limited value as a screening test for diabetes.…”
Section: Is There An Accepted Screening Test and Diagnostic Test For mentioning
confidence: 99%
“… Prediction may be improved by the use of a risk score [17–21], but the risk score should be tested and validated within the specific population. …”
Section: Targeted Screening and Intensified Case‐findingmentioning
confidence: 99%
“…The details of the initial survey and the follow-up study have been reported previously. [14][15][16] A postal questionnaire concerning the previous history of diabetes, hypertension, anti-hypertensive medication and other questions was sent to each of the participants, and the answers to the questions and the anti-hypertensive agents used previously were checked during the interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies have examined this and performed an OGTT in the whole population irrespective of the RCG result. Qiao et al (1995) studied 1,008 people and using a cutoff level for RCG of 5.8 mmol/L achieved a sensitivity of 79% in men but only 40% in women, while specificity was 86% and 84%, respectively, for men and women. The authors Case Detection and Diagnosis, concluded that RCG is too insensitive to use for routine screening for diabetes in a general population, particularly in populations with a known low prevalence of diabetes.…”
Section: • Blood Testing Without Risk Factor Assessment Also Performsmentioning
confidence: 99%